(untitled) (Fiep Bulletin - online, 2011)
Study literature review, held in databases BDENF SCIELO, MEDLINE, LILACS, CAPES, using descriptors such as family, congenital heart disease and nursing. In order to address the issue on the family of children with congenital heart disease and relate to nursing care at admission of these children. The child with congenital heart surgery when he suffers and his family go through a process of insecurity and is essential to prepare psychologically for this family plays a protective role with this small patient. But often the family is now in the process of their children’s disease, others the necessary information, presenting anxiety may undermine the recovery in the postoperative period. Nursing care of children with congenital heart disease and their families occurs most often in a non-systematic and there is a gap regarding continuous and integrated health care system, occurring only in isolated moments, allowing a dichotomy in the triad nursing, family and child, who which leads us to think of how to make a systematic organized nursing which is intended to meet all needs addressing biopsychosocial aspects in the hospital and beyond.